Application of pre-deformation rolling in the welding heat-affected zone of tailor-welded blanks formed by deep-drawing process. (March 2020) - Hao, Zengliang; Luo, Junting; Jin, Yongbo; Meng, Dawei; Zhang, Chunxiang
Abstract: Excessive wall thickness reduction occurs in the welding heat-affected zone (HAZ) of tailor-welded blanks (TWBs) during the deep-drawing process. The pre-deformation rolling (PDR) for welding HAZ was introduced in this study. The double-ellipsoidal heat source mechanical model was used to simulate welding, PDR, and plastic deformation processes of standard tensile specimens and large-size TWBs. Results show the uniform distribution of equivalent strain and wall thickness of the specimens with 4 % PDR reduction in the HAZ after uniaxial tensile deformation under the same elongation. Thus, the 4 % rolling reduction not only improves the material strength of the HAZ but also ensures good ductility. The optimum 4 % PDR parameters are applied to the deep-drawing process of large TWB container heads. The wall thickness of the HAZ and the base material are uniformly reduced after the deep drawing of the TWB because 4 % PDR improved the plastic deformation capability of the HAZ. Finally, the experimental study on the deep drawing forming and microstructure of large TWBs is conducted. Compared with the HAZ without PDR, the HAZ wall thickness of the deep-drawing forming head with 4 % PDR reduction in the HAZ is increased from 3.98 mm to 4.25 m. Moreover, the grains are fine and uniform similar to those of the base material. Furthermore, the distribution of hardness values in each area of the deep-drawing formed head is uniform.